2016
DOI: 10.1016/j.ccell.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Metabolic Atlas of Clear Cell Renal Cell Carcinoma

Abstract: Summary Dysregulated metabolism is a hallmark of cancer, manifested through alterations in metabolites. We performed metabolomic profiling on 138 matched clear cell renal cell carcinoma (ccRCC)/normal tissue pairs and found that ccRCC is characterized by broad shifts in central carbon metabolism, one-carbon metabolism and anti-oxidant response. Tumor progression and metastasis were associated with metabolite increases in glutathione and cysteine/methionine metabolism pathways. We develop an analytic pipeline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

51
648
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(725 citation statements)
references
References 52 publications
(60 reference statements)
51
648
5
1
Order By: Relevance
“…Interestingly, we found a significant increase in the carbohydrate pathway metabolites (glucose 6-phosphate [G6P], and galactose 1-phosphate (Gal1P) and redox markers (glutathione [GSH] and glutathione disulfide [GSSG]), which are consistent with prior metabolic analysis reported on ccRCC tumors (35)(36)(37).…”
Section: I N I C a L M E D I C I N Esupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, we found a significant increase in the carbohydrate pathway metabolites (glucose 6-phosphate [G6P], and galactose 1-phosphate (Gal1P) and redox markers (glutathione [GSH] and glutathione disulfide [GSSG]), which are consistent with prior metabolic analysis reported on ccRCC tumors (35)(36)(37).…”
Section: I N I C a L M E D I C I N Esupporting
confidence: 79%
“…ccRCC is characterized by significant alterations in intermediary metabolism and antioxidant response, and metabolite increases in glutathione and cysteine/methionine metabolic pathways are associated with tumor progression and metastasis (35,36). In order to understand the correlation between FF and cellular metabolism in these tumors, we performed a targeted metabolomic analysis of ccRCC, from fresh frozen high-quality tumor samples and corresponding adjacent URP.…”
Section: I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Glutathione (GSH) is considered the predominant endogenous cellular antioxidant, playing a critical role in the cellular defensive response to oxidative stress by neutralizing free radicals and reactive oxygen species(21). In ccRCC in particular, the conditionally essential amino acid glutamine is subjected to reductive carboxylation leading to production of the oncometabolite 2HG(22) as well as being a precursor for the major antioxidant system comprised of GSH and GSSG(19,23); indeed, a recent study showed that metabolites that eventually contribute to GSH biosynthesis were able to significantly separate ccRCC tumors from normal tissues(24), emphasizing the importance of this metabolic pathway to ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on work from our group and others (2, 3), it is becoming evident that RCC is truly a metabolic disease such that exploitation of newly discovered altered metabolic pathways is a fertile area for therapeutic target discovery. In our continuing evaluation of such reprogramming, it has become apparent that two such pathways, PAK4/β-catenin and NAD synthesis, are important in RCC progression but as yet have not been evaluated with respect to potential therapeutic targeting in this disease.…”
Section: Introductionmentioning
confidence: 99%